Domestic Incentive Measures for Renewable Energy With Possible Trade Implications - Bahar, Heymi (OECD Trade and Environment Working Papers, 2013)
In recent years the manufacturing of renewable-energy technologies has become truly global. The associated rise in international investment and trade in goods and services related to renewable energy has been rapid, but it has not always been smooth. Already there have been challenges at the WTO, and the unilateral imposition of countervailing and anti-dumping duties, in response to some countries' policies on the grounds that they distort trade. Against this background, this paper surveys, through the lenses of market-pull and technology-push policies, the numerous domestic incentives used by governments to promote renewable energy, focusing on those that might have implications for trade - both those that are likely to increase opportunities for trade and those that may be inhibiting imports or promoting exports. Many OECD countries, and an increasing number of non-OECD countries, have established national targets for renewable energy.